TINJAUAN TEOLOGIS TENTANG PERJANJIAN YANG DIBAHARUI BAGI UMAT ALLAH MENURUT YEREMIA 31:33-34 - Hery Susanto; Ferius Feliks Iba (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2020)
This article is a qualitative description about the new covenant that has been listed in Jeremiah 31:33-34. A covenant supposed to be birelational that consciously commited to obey all of the consequences regarding the contract. Obviously Israelites failed to grasp God’s desire about rebuild healthy relationship with God. This situation as the background of the importance of the new covenant that God put in human’s heart. God’s creative way has reached the culminative point through Jesus Christ that carried all the penalty of sins and save the world from diminished. The implication to all of believers is that new covenant is based on love not legalistic relationship, grace not contractual engagement.